PENERAPAN ANALISA SISTEM DINAMIK UNTUK KAJIAN KEBERLANJUTAN PENGELOLAAN RUSUNAWA DI KOTA BATAM - Toruan, Hotma; Pertiwi, Setyo; Suprihatin, Suprihatin; Djakapermana, Ruchyat Deni (Jurnal Sosial Ekonomi Pekerjaan Umum, 2017)
Batam is one of cities whose industry has been developing so fast in which its island is located strategically. The development of Batam Island as an industrial area has pushed ahead the development of other sectors. As the industrial sectors have developed in Batam city, the residential areas for the workers have also developed quickly outside the industrial areas, Batam. The mushrooming of houses for workers who want to rent outside the industrial areas has caused a new problem for Batam, in which the quality of environment is getting low; furthermore, this tends cause slum. This is because a lot number of workers there are from other areas outside Batam. Moreover, this is also caused by the increase of employment composition in industrial sector of 53,03%. The aims of this research were to know the condition of the whole aspects - social, economy, and ecology in the future and to observe a sensitive driving system to determine the sustainability management of housing. This research was carried out in an industrial areas in Batam city including Muka Kuning, Tanjung Uncang and Tembesi. This research was performed in five months from May to September 2015. The modeling of development and housing which is sustainable in Batam Industria Areas was done with the approach of dynamic system. The result of simulation showed that the quality of environment in 2010 was 44.85% and will decrease of 34.62% in 2020. This was due to the increase of waste which could not be managed. The level of security and comfort to live in the housing in 2010 was 68.28% and will decrease of 48.43% in 2020. With all of the problems mentioned, the level of housing sustainability in 2010 was 42.33% and will decline of 29.58% in 2030. The process to develop the housing is still needed because there are still many people whose income is still low and they need the housing. The main strategy to develop and use the housing needs cooperation partnership or the relationship among the government, the manager of housing and the residents. Therefore, the development that will be done in the future will be better.  Keywords : housing, environment, dynamic system, simulation